Inside the invisible memorialising slavery and freedom in the life and works of Lubaina Himid - Bernier, Celeste-Marie 1975-; Rice, Alan J. 1960-; Himid, Lubaina 1954-; Durkin, Hannah ca. 20./21. Jh (Liverpool University Press, 2019)
Inside the Invisible provides the first examination of the work of Turner Prize-winning Black British artist and curator Professor Lubaina Himid CBE. This comprehensive volume breaks new ground by theorizing her development of an alternative visual and textual language within which to do justice to the hidden histories and untold stories of Black women, children, and men bought and sold into transatlantic slavery. For Himid, the act of forgetting within official sites of memory is indivisible from the art of remembering within an African diasporic art historical tradition. She interrogates the widespread distortion and even wholesale erasure of Black bodies and souls subjected to dehumanizing stereotypes and grotesque caricatures within western imaginaries and dominant iconographic traditions over the centuries. Creating bodies of work in which she comes to grips with the physical and psychological realities of iconic and anonymous African diasporic individuals as living breathing human beings rather than as objectified types, she bears witness not only to tragedy but to triumph. A self-appointed researcher, historian, and storyteller as well as an artist, she succeeds in seeing "inside the invisible" regarding untold narratives of Black agency and artistry by mining national archives, listening to oral stories, acknowledging art-making traditions, and revisiting autobiographical testimonies
Keywords: Himid, Lubaina -- 1954-; Himid, Lubaina / 1954-; Slavery in art; African diaspora in art